2012
DOI: 10.1016/j.ijcard.2011.01.075
|View full text |Cite
|
Sign up to set email alerts
|

Acute glucose dysmetabolism in the elderly with ST elevation myocardial infarction submitted to mechanical revascularization

Abstract: Though age is a predictor of adverse events after acute coronary syndrome, including in-hospital and posthospital mortality rates, elderly patients are under-represented in randomized trials evaluating strategies of early coronary revascularization in acute myocardial infarction. Several factors can account for the unfavorable outcome of the elderly, comprising increased glucose values. Diabetes is more common in the elderly patients with acute myocardial infarction in respect to younger patients and elevated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Furthermore, the patients included were relatively young and previous studies have shown a close relationship between newly diagnosed abnormal glucose regulation and age [8,26-28]. Additionally, a high proportion of our patients were diagnosed with single-vessel disease during coronary angiography [10], which may have contributed to the low event-rate observed in both groups.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, the patients included were relatively young and previous studies have shown a close relationship between newly diagnosed abnormal glucose regulation and age [8,26-28]. Additionally, a high proportion of our patients were diagnosed with single-vessel disease during coronary angiography [10], which may have contributed to the low event-rate observed in both groups.…”
Section: Discussionmentioning
confidence: 95%
“…Criteria used for the definition of insulin resistance are in accordance with the recently published guidelines proposed by the European Group of the study of Insulin Resistance (EGIR) [25,26]. HOMA was calculated according to the following formula: {[fasting insulin (microU/ml)] 9 [fasting glucose (mmol/l)]}/22.5 [27].…”
Section: Definition Of Insulin Resistancementioning
confidence: 99%
“…On ICCU admission, after PCI, the following parameters were measured [5][6][7][8][9][10][11]: glucose (mg/dl), insulin values (mIU/l), glycated hemoglobin (HbA1c, %), troponin I (ng/ml), C-reactive protein (mg/dl) (normal values b 9), NT-pro Brain Natriuretic Peptide (NT-pro BNP) (pg/ml), erythrocyte sedimentation rate (ESR), microalbuminuria (mg/dl), uric acid (mg/dl), leukocytes (*10 3 /μl), fibrinogen (mg/dl). Glucose, creatinine and Tn I were measured three times a day during ICCU stay and peak values for each variable were considered.…”
mentioning
confidence: 99%
“…Glucose, creatinine and Tn I were measured three times a day during ICCU stay and peak values for each variable were considered. Acute insulin resistance was measured by means of homeostatic model assessment (HOMA) [5,[9][10][11][12]. (Table 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation